Parenthood in a Swedish prospective cohort of 1,378 adolescents and young adults banking semen for fertility preservation at time of cancer diagnosis - Weibring, Kristina; Lundberg, Frida E.; Cohn-Cedermark, Gabriella; Rodriguez-Wallberg, Kenny Alexandra (Frontiers in Endocrinology, 2024)
Background: The possibility of future parenthood is a highly relevant issue for patients of reproductive age facing oncologic treatment. This study aimed to investigate how fatherhood was achieved in a patient cohort of adolescents and young adults (AYAs) banking semen at time of cancer diagnosis and to determine the effectiveness of cryopreservation aimed at fertility preservation in the cohort. Materials and methods: Observational cohort study examining AYAs with a cancer diagnosis who underwent semen banking for fertility preservation at Karolinska University Hospital 1988-2020, as part of the Stockholm regional fertility preservation program. This cohort is being prospectively followed since time of referral to the program, with most individuals included when presenting with primary cancers (Study Registration: ClinicalTrials.gov NTC04602962). Individuals achieving adulthood in the cohort were followed-up regarding their reproductive outcomes by linking to the Swedish Multi-generation Register, to identify fatherhood through natural conception or adoption, and to the Swedish National Quality Registry for Assisted Reproduction to identify parenthood through medical assistance, including the use of own sperm either cryopreserved or fresh, or donor sperm. Results: Of the 1,378 patients referred during the study period, 1,357 were eligible for fatherhood analysis (aged >20 years at the end of follow-up, December 31, 2021). In total, 493 men became fathers following cancer treatment: 399 (81%) did so naturally, 87 (18%) via assisted reproductive techniques (including two using donor sperm), and 7 (1%) through adoption. Of the 92 patients who used their cryopreserved sperm for assisted reproductive techniques, 34 (37%) successfully fathered a child. The patients may have had children prior to cryopreservation. Conclusion: A large proportion of AYA cancer survivors achieved fatherhood through natural conception in this cohort, whereas less than 1 in 5 survivors needed medical assistance to conceive. Although a low utilization rate of cryopreserved sperm was found in this cohort, its use was highly effective in the group that developed infertility. At present there are no standardized predictors of testicular toxicity after cancer treatment, and individual variability is high. Further research is needed to identify patients at risk of infertility who would benefit from fertility preservation.